Matching matters! - Freitas, Ayres; López-Val, David; Plehn, Tilman (Arxiv, 2016)
Effective Lagrangians are a useful tool for a data-driven approach to physics beyond the Standard Model at the LHC. However, for the new physics scales accessible at the LHC, the effective operator expansion is only relatively slowly converging at best. For tree-level processes, it has been found that the agreement between the effective Lagrangian and a range of UV-complete models depends sensitively on the appropriate definition of the matching. We extend this analysis to the one-loop level, which is relevant for electroweak precision data and Higgs decay to photons. We show that near the scale of electroweak symmetry breaking the validity of the effective theory description can be systematically improved through an appropriate matching procedure. In particular, we find a significant increase in accuracy when including suitable terms suppressed by the Higgs vacuum expectation value in the matching.